2009
DOI: 10.2460/ajvr.70.1.105
|View full text |Cite
|
Sign up to set email alerts
|

Use of pradofloxacin to treat experimentally induced Mycoplasma hemofelis infection in cats

Abstract: Pradofloxacin had anti-M hemofelis effects similar to those of doxycycline. In addition, pradofloxacin may be more effective at long-term M hemofelis organism clearance than doxycycline.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
29
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 25 publications
0
29
0
Order By: Relevance
“…Currently, there is no in vitro test system to assess the viability of hemoplasmas. PCR-positive results do not provide information regarding the presence of viable organisms; however, it is generally believed that the DNA of dead organisms is immediately cleared from the body [9]. Therefore, the ~40-fold increase in " Candidatus M. turicensis" copies in the salivary gland of cat R2, combined with the PCR-positive results of a tissue sample and a blood sample from two additional cats (cat S1 and T1) after methylprednisolone administration, supports the hypothesis that there were still viable organisms in these cats.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, there is no in vitro test system to assess the viability of hemoplasmas. PCR-positive results do not provide information regarding the presence of viable organisms; however, it is generally believed that the DNA of dead organisms is immediately cleared from the body [9]. Therefore, the ~40-fold increase in " Candidatus M. turicensis" copies in the salivary gland of cat R2, combined with the PCR-positive results of a tissue sample and a blood sample from two additional cats (cat S1 and T1) after methylprednisolone administration, supports the hypothesis that there were still viable organisms in these cats.…”
Section: Discussionmentioning
confidence: 99%
“…To date, it is assumed that infected animals do not completely clear the " Candidatus M. turicensis" organisms, even after antibiotic treatment [6-8]. Different studies have suggested a possible sequestration of feline hemoplasmas in tissues [9-11]. The dynamics of the chronic phase of hemoplasma infection, however, are still poorly understood.…”
Section: Introductionmentioning
confidence: 99%
“…These findings are similar to those of a recent study in alpacas, in which treatment with oxytetracycline was not associated with faster clearance of ''Candidatus Mycoplasma haemolamae'' infection. 24 However, in cats, studies 6,7,[20][21][22] using qPCR have demonstrated the effectiveness of both doxycycline and fluoroquinolones in reducing copy numbers of feline hemoplasmas and improving clinical signs, but again, clearance of infection is not always achieved. Given the long duration of treatment with no marked change in M. haemocanis copy numbers, it is likely that the resolution of clinical disease in the present case was due to the development of an effective immune response by the dog.…”
mentioning
confidence: 99%
“…The recruitment of eosinophils, although usually associated with parasitic and allergic inflammation, can also be associated with certain bacterial infections [40]. Eosinophilia has been previously reported during feline hemoplasma infections but was not considered clinically relevant [41,42]. In addition, a previous study reported an association between eosinophilia and latent Haemobartonella canis infection [43].…”
Section: Discussionmentioning
confidence: 99%